Evidence for regulation of oxidative stress by latent membrane protein 1 oncoprotein in patients with low-grade leukemic B cell lymphoma with latent Epstein–Barr virus infection. Issue 8 (August 2014) - Papadopoulou, Vasiliki; Diamantopoulos, Panagiotis T.; Kontandreopoulou, Elina; Polonyfi, Katerina; Variami, Eleni; Kouzis, Panagiotis; Galanopoulos, Athanasios; Spanakis, Nikolaos; Zervakis, Konstantinos; Iliakis, Theodoros; Perrea, Despoina; Kollia, Panagoula; et al.
Abstract The role of latent Epstein–Barr virus (EBV) infection in the pathogenesis of low-grade B cell non-Hodgkin lymphoma (B-NHL) has not been studied. We therefore investigated the incidence of latent EBV infection in a group of patients with leukemic low-grade B-NHL, as well as the incidence of viral latent membrane protein 1 (LMP1) oncoprotein expression in the same patient group. Furthermore, in an attempt to elucidate the role of this viral oncoprotein in non-EBV-related lymphomas, we correlated the expression of LMP1 with the level of oxidative stress, a parameter related to apoptosis. In the present study we detected lower levels of oxidative stress in the sera of LMP1-positive patients. This possibly implies an anti-apoptotic role of this viral oncoprotein in low-grade B cell lymphomas. However, LMP1 expression status did not affect expression of the major anti-apoptotic gene BCL-2.